Post‐concussion symptom burden in children following motor vehicle collisions - Lumba‐Brown, Angela (J Am Coll Emerg Physicians Open, 2020)
OBJECTIVE: Motor vehicle collisions generate considerable transmitted forces resulting in traumatic brain injury in children presenting to emergency departments (EDs). To date, no large study has examined post‐concussive symptoms in children sustaining concussions in motor vehicle collisions. This study aimed to compare trends in acute post‐concussive symptom burden in children with concussion following motor vehicle collisions as compared to other injury mechanisms. METHODS: The study is a secondary analysis of the Predicting Persistent Post‐concussive Problems in Pediatrics study, which prospectively recruited a multicenter cohort of 3029 children 5–17 years of age presenting to the ED with concussion from 2013–2015. Post‐concussive symptom ratings were obtained at pre‐specified time points for 12 weeks post‐injury, using the validated Post‐Concussion Symptom Inventory (PCSI). Symptom severity and recovery trajectories were measured using delta scores on the PCSI (mean post‐injury symptom score minus perceived pre‐injury score). A multivariable, longitudinal model evaluated the adjusted effect of mechanism of injury (motor vehicle collisions vs other mechanisms) on mean symptom scores, compared to perceived pre‐injury reports, and the temporal change in mean scores over during recovery. RESULTS: Of 3029 study participants, 56 (1.8%) sustained concussion from motor vehicle collisions. Children sustaining concussion in a motor vehicle collision had lower post‐concussive symptom scores upon ED presentation, measured as differences from their perceived pre‐injury reports, as compared to other injury mechanisms (−0.36 [95% confidence interval (CI) = −0.58, −0.15]). However, the motor vehicle collisions group showed the smallest decline in symptom burden over 1 month following injury (−0.54 [95% CI = −0.81, −0.27]). CONCLUSIONS: Children sustaining concussions in motor vehicle collisions may have lower initial symptom burdens but slower symptom recovery at 1 month compared to other mechanisms of injury and may represent a distinct population for prognostic counseling in the ED requiring further research.